Translanguaging Practices in Jigsaw-Based Collaborative Learning in Indonesian EFL Classrooms - Devi Purmayanti; Ilmy Anillah Maula; Maulidiyyatul Uswah (Universitas Palangka Raya, 2026)
In multilingual English as a Foreign Language (EFL) classrooms, students often draw on multiple linguistic resources to support comprehension and interaction during collaborative learning activities. However, translanguaging practices within structured cooperative learning techniques, such as the Jigsaw method, remain underexplored in Indonesian higher education contexts. This study investigates how students employ translanguaging during Jigsaw-based collaborative activities and how they perceive its role in supporting their participation and understanding in an Indonesian EFL classroom. The study adopted a qualitative classroom-based case study design conducted at a pesantren-based university in East Java, Indonesia. Data were collected through semi-structured interviews with five fifth-semester students who participated in Jigsaw learning activities across different English-related courses. The data were analyzed using thematic analysis to identify patterns in students’ language practices and perceptions. The findings reveal that translanguaging played several important roles in facilitating collaborative learning. First, students used translanguaging to clarify complex concepts and ensure shared understanding during group discussions. Second, translanguaging functioned as peer scaffolding, enabling students to assist classmates by explaining ideas and translating unfamiliar terms. Third, the flexible use of multiple languages helped reduce anxiety and encouraged more active participation in group interaction. Finally, students expressed positive perceptions toward translanguaging, viewing it as a helpful strategy that supported comprehension while still maintaining the importance of English for academic communication. These findings suggest that integrating translanguaging into cooperative learning strategies such as the Jigsaw technique can create more inclusive and interactive learning environments in multilingual EFL classrooms.